Meningkatkan Kreativitas Siswa Pada Mata Pelajaran Seni Rupa Dengan Menggunakan Model PjBL Kelas V SD Inpres Malakosa - Ariasih, Ni Ketut; Lagandesa, Yun Ratna; Hariana, Kadek; Firmansyah, Arif; Fasli, Muhamammad (JURNAL DIKDAS, 2025)
This study was motivated by the low level of students' creativity in Visual Arts, which has become a significant obstacle in developing their potential. This classroom action research (CAR) aimed to enhance the creativity of fifth-grade students at SD Inpres Malakosa through the implementation of the Project-Based Learning (PjBL) model. The research design followed the Kemmis and McTaggart model, which includes the stages of planning, implementation, observation, and reflection, conducted over two cycles. The subjects of this study were 20 fifth-grade students at SD Inpres Malakosa in the 2024/2025 academic year, consisting of 7 boys and 13 girls. Data were collected using observation, interviews, and documentation methods. The results of the study indicated a significant improvement in students' creativity. In the pre-action stage, the students' creativity level was categorized as low, with a score percentage of 41.42%. In Cycle I, the creativity score increased to 67.1%, with a classical completeness rate of 50%. In Cycle II, the creativity score reached 81.5%, with a classical completeness rate of 80%. Based on these findings, it can be concluded that the application of the Project-Based Learning (PjBL) model effectively improves students' creativity in Visual Arts. This model provides meaningful and relevant learning experiences, encouraging students to be more creative in producing artistic works.